2018
DOI: 10.1080/21556660.2018.1513846
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the clinical courses of type 2 diabetic patients whose basal insulin preparation was replaced from insulin glargine 100 units/mL to insulin glargine biosimilar or 300 units/mL: a propensity score-matched observation study

Abstract: Objective: We compared the clinical course of type 2 diabetic patients whose basal insulin preparations were replaced from insulin glargine (IGlar) 100 units/mL (U100) to IGlar biosimilar or IGlar 300 units/mL (U300).Methods: After propensity score matching, 34 patients whose basal insulin preparation was switched from IGlar U100 to IGlar biosimilar and 102 switched to IGlar U300 were observed for 6 months.Results: The HbA1c level and body weight did not change significantly after the replacement in the IGlar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…However, after controlling for covariates, the reduction in hypoglycemia events with Gla-300 remained significant. Here, once again, our data are in line with other real-world studies, which have shown reduced hypoglycemia risk with Gla-300 vs. (mainly) first-generation BIAs [ 18 , 21 23 , 33 ]. In the above-mentioned pragmatic studies that were mainly conducted in Europe, most hypoglycemia end points were similar for Gla-300 and standard-of-care BIA, but there were some significant reductions in nocturnal hypoglycemia with Gla-300 [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, after controlling for covariates, the reduction in hypoglycemia events with Gla-300 remained significant. Here, once again, our data are in line with other real-world studies, which have shown reduced hypoglycemia risk with Gla-300 vs. (mainly) first-generation BIAs [ 18 , 21 23 , 33 ]. In the above-mentioned pragmatic studies that were mainly conducted in Europe, most hypoglycemia end points were similar for Gla-300 and standard-of-care BIA, but there were some significant reductions in nocturnal hypoglycemia with Gla-300 [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…Apprehension with biosimilar use generally pertains more to switching therapies for stable patients as opposed to initiation in treatment-naïve patients [13]; however, several studies have found that switching between agents does not confer any additional risk or lead to poorer clinical outcomes [1315]. Although the safety and efficacy profile of biosimilar drugs cannot be assured to be 100% due to their complexity, existing data reassure that is very likely that biosimilar and originator biologics are relatively equal as it pertains to both [16–19].…”
Section: Discussionmentioning
confidence: 99%
“…It has to be mentioned that Basalin was not approved as a BioIns in any of the regulated markets. In a similarly designed Japanese study with Abasaglar, no differences in HbA1c values between patients treated with the originator insulin glargine and the BioIns were observed; however, fasting glycemic values were not reported (15). Also, there are good reasons why the regulatory authorities in the United States and the EU require more precise measures than HbA1c results from clinical trials to approve an insulin as a BioIns.…”
Section: Biosimilar Insulinmentioning
confidence: 97%